Tradisi Hagiografi Sufi YasawÃ®: Relasi Tasawuf dan Politik - Asmawi Asmawi (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2006)
Every method and approach in Islamic Studies currently available to us has weaknesses in looking at religious data. For that reason, efforts to find better and more integrative method are needed. One of the approaches that might be useful for Islamic Studies is historical approach. Sufism in the meantime, has become an important part of the history of Islam. Nonetheless, it is only recently that Sufism?as well as its origin, change and development- become a subject of historical study. Hagiography has also become a new trend in the historical study of Sufism. And one of the Sufis whose hagiography has become an important subject of study is that of Ahmad Yasafi, a Sufi of 16th ? 17th century. Hagiography is a kind of written sources that narrate the life of a supposedly holy man and the legends related to him. According to Devin Dewees, the hagiography of Ahmad Yasawi portrays the man?s personal and communal life, his patronage with the ruler, the rituals of his tar?qah, and the legends related to him and his order. This article ?using historical approach- is a descriptive account of Ahmad Yasawi?s hagiography.